Dampak Ketidaksesuaian Konfigurasi Parkir Pesawat di Parking Stand Bandar Udara Iskandar Pangkalan Bun Kalimantan Tengah - Geryana, Aizal; Rachmawati, Desiana (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Iskandar Pangkalan Bun Airport, Central Kalimantan, has 5 parking stands that are used for its operational activities, the direction of the parking stands has been regulated in the Standard Operating Procedure (SOP). In its implementation, violations occurred, namely parked aircraft that did not comply with the SOP and pilots who did not want to follow directions from AMC officers referring to the applicable SOPs. The purpose of this study was to find out the causes, impacts, and solutions of the mismatch of aircraft parking configurations at the parking stand of Iskandar Pangkalan Bun Airport, Central Kalimantan. This study uses descriptive qualitative research methods, data collection is done by participatory observation, structured interviews and documentation. The documentation used is in the form of the applicable AMC Iskandar SOP. The research was conducted on 3 informants, namely Mr. Idi Adnan Ismail with the position of Head of Services and Services section, Mr. Wahyu Hidayat with the position of Head of AMC. And Mr. Roni Chaeruddin as an AMC officer. The validity of the data using triangulation, namely source triangulation, technical triangulation and time triangulation. The results of the study indicate that there is a cause for the mismatch of aircraft parking configurations at the Iskandar Pangkalan Bun Airport parking stand. In the form of violations committed by AMC officers and pilots who committed violations on purpose. This violation resulted in a negative impact, namely flight delays, as well as the feared impact of crashes between aircraft and disruption of operations. Solutions made to overcome this impact include verbal warnings to Wings Air airline pilots and giving warnings in briefings carried out with the site manager (SM) of Citilink airlines, AMC officers, and marshallers. Keywords: Parking Stand, Parking Konfiguration, Iskandar Airport, SOP